The Influence of Premenopausal and Menopausal Women's Demographic Characteristics on Anxiety and Quality of Life - Ninda Ayu Prabasari; Linda Juwita (Babali Health, 2023)
Introduction: The premenopausal and menopausal periods are natural processes that occur in women. Both of these periods bring about changes in physical, psychological, and social aspects. The symptoms and changes experienced in the body can make women feel fearful, anxious, and lead to changes in their quality of life. The research aims to determine the influence of premenopausal and menopausal women's demographic characteristics on anxiety and quality of life. Methods: This study employed a descriptive design with an analytical observational approach and a cross-sectional design. The study population consisted of community health Center Jagir cadres aged ≥35 years, selected through purposive sampling, with a sample size of 70 respondents. The analysis use the ordinal regression statistical test. Results: Demographic characteristics revealed that the majority were aged 46-55 years (46%), had a high level of education (83%), and were married (81%). The majority experienced mild anxiety (40%) and had good quality of life (67%). The demographic characteristics of women (age, education, and marital status) significantly influenced anxiety and quality of life with a p-value <0.05. The Pseudo R Square values for anxiety were age 0.011, education 0.105, marital status 0.004, and for quality of life were age 0.007, education 0.028, marital status 0.004. Conclusion: Demographic characteristics, including age, education, and marital status, have an impact on anxiety and quality of life with a P Value < 0.05. Providing menopausal syndrome education and husband support is needed in dealing with the pre-menopause period to reduce anxiety and improve quality of life.